Influence of whitening gel application protocol on dental color change - Caneppele, Taciana Marco Ferraz [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; Huhtala, Maria Filomena Rocha Lima [UNESP]; Bresciani, Eduardo [UNESP] (Wiley, 2015)
To evaluate the influence of different whitening protocols on the efficacy of 35% hydrogen peroxide (HP) tooth whitening and gel pH and concentration. Eighty-four enamel/dentin discs from bovine incisors were used. The baseline color was measured with a spectrophotometer. Two sessions of in-office whitening with 35% HP were performed under different protocols: G1: 3 applications of HP (10 min each) per session; G2: 1 application of 30 min per session; G3: 1 application of 40 min per session, with no gel replenishment within session for groups 2 and 3. HP titration and pH evaluation at baseline, after 10, 30, and 40 min were also performed. The final color was measured 24 h after the 1st and 2nd whitening sessions. Data were submitted to Repeated Measures ANOVA and Tukey's test. For color evaluation, no differences were observed among groups after two sessions. HP titration showed no drop on concentration after 10, 30, or 40 min. The pH was 5.54 at baseline and 5.41 after 40 min. Replenishment or extended application time of in-office whitening gel does not affect gel pH and concentration, a fact that supports the similar effectiveness of whitening observed among the tested protocols.